Shared Memory Architecture based Parallel Programming for RCS Estimation - Shibu, P S; Atul; Choudhury, Balamati; Nair, Raveendranath U (2018 International Conference on Applied Electromagnetics, Signal Processing and Communication (AESPC), 2018)
Parallel programming techniques have been prominently explored in various engineering applications as it provides a time efficient solution to the complex problems without affecting the accuracy. Parallel programming approach for solving complex electromagnetic problems with the requirement of huge computational power has been a thrust area of research. This paper focuses on shared memory parallel programming model for RCS estimation of electrically large structures such as cylindrical duct and a solid cylinder with surfaces of concave and convex in nature. In this paper OpenMP API and parallel computing toolbox in MATLAB are utilized to simulate a parallel program on a shared memory architecture. An exponential decrease in computation time has been through a classical RCS estimation problem.